2021
DOI: 10.1158/1538-7445.am2021-1773
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1773: Tumor cell-intrinsic STING pathway activation leads to robust induction of Type III Interferons and contributes to the anti-tumor activity elicited by STING agonism

Abstract: STING pathway plays a critical role in inducing anti-tumor immunity by upregulating Type 1 Interferon (IFN) and IFN-stimulated genes within the tumor microenvironment in response to cytosolic nucleic acid ligands. Therefore, the STING pathway agonism has emerged as a potential therapeutic mechanism to stimulate an anti-tumor innate immune response. Intratumorally injected free STING-agonists that are currently being evaluated in the clinic by others have shown limited effects in non-injected lesions. Antibody-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Notably, in addition to their potential therapeutic utility, ADCs may also be of use as a research tool for addressing these outstanding questions. Indeed, Cetinbas et al are pursuing such a strategy to dissect the importance of cell-specific STING pathway activation in tumors and have identified distinct differences in resultant immune profiles generated by nontargeted STING agonists and cancer cell-targeted STING agonists, which suggested that cancer cells can positively contribute to antitumor immunity in certain cases …”
Section: Summary Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in addition to their potential therapeutic utility, ADCs may also be of use as a research tool for addressing these outstanding questions. Indeed, Cetinbas et al are pursuing such a strategy to dissect the importance of cell-specific STING pathway activation in tumors and have identified distinct differences in resultant immune profiles generated by nontargeted STING agonists and cancer cell-targeted STING agonists, which suggested that cancer cells can positively contribute to antitumor immunity in certain cases …”
Section: Summary Perspectives and Future Directionsmentioning
confidence: 99%
“…Indeed, Cetinbas et al and cancer cell-targeted STING agonists, which suggested that cancer cells can positively contribute to antitumor immunity in certain cases. 544 Another concern facing systemic administration of STING agonists, particularly non-nucleotide, small molecules, is the potential for inducing toxicity in T cells, which are important for therapeutic efficacy. 212 T cells express high levels of the STING protein and appear to be highly susceptible to STINGinduced apoptosis.…”
Section: Summary Perspectives and Futurementioning
confidence: 99%
“…In animal model studies, XMT‐2056 exhibited strong antitumor activity and pharmacokinetic properties, that can significantly induce type III interferon production and inhibit tumor growth. [ 57 ]…”
Section: Pattern Recognition Receptor Agonists As Payloadsmentioning
confidence: 99%